PD-L1-deficient mice show that PD-L1 on T cells, antigen-presenting cells, and host tissues negatively regulates T cells - Latchman, Yvette E. (National Academy of Sciences, 2004)
Both positive and negative regulatory roles have been suggested for the B7 family member PD-L1(B7-H1). PD-L1 is expressed on antigen-presenting cells (APCs), activated T cells, and a variety of tissues, but the functional significance of PD-L1 on each cell type is not yet clear. To dissect the functions of PD-L1 in vivo, we generated PD-L1-deficient (PD-L1(–/–)) mice. CD4(+) and CD8(+) T cell responses were markedly enhanced in PD-L1(–/–) mice compared with wild-type mice in vitro and in vivo. PD-L1(–/–) dendritic cells stimulated greater wild-type CD4(+) T cell responses than wild-type dendritic cells, and PD-L1(–/–) CD4(+) T cells produced more cytokines than wild-type CD4(+) T cells in vitro, demonstrating an inhibitory role for PD-L1 on APCs and T cells. In vivo CD8(+) T cell responses also were significantly enhanced, indicating that PD-L1 has a role in limiting the expansion or survival of CD8(+) T cells. Studies using the myelin oligodendrocyte model of experimental autoimmune encephalomyelitis showed that PD-L1 on T cells and in host tissues limits responses of self-reactive CD4(+) T cells in vivo. PD-L1 deficiency converted the 129S4/SvJae strain from a resistant to experimental autoimmune encephalomyelitis-susceptible strain. Transfer of encephalitogenic T cells from wild-type mice into PD-L1(–/–) recipients led to exacerbated disease. Disease was even more severe in PD-L1(–/–) recipients of PD-L1(–/–) T cells. These results demonstrate that PD-L1 on T cells, APCs, and host tissue inhibits naïve and effector T cell responses and plays a critical role in T cell tolerance.